Anaerobic digestion of brewer’s spent grain with biochars—biomethane production and digestate quality effects - Świechowski, Kacper; Rasaq, Waheed A.; Syguła, Ewa (Frontiers in Energy Research, 2023)
In the research, biochar made from the brewers’ spent grain at temperatures of 300, 450, and 600 °C was produced and subjected to the anaerobic digestion of the brewers’ spent grain. Biochar shares of 2, 5, 10, and 50% concerning total solids of the substrate were tested at three substrate-to-inoculum ratios of 0.5, 1.0, and 2.0, respectively. The anaerobic digestion process was performed at 37 °C and took 30 days. For anaerobic digestion, biomethane production was recorded, and used for kinetics parameters determination according to the first-order model. After the process, process residues (digestate) were analyzed for fertilizing potential. The biomethane yield differs from 264 to 325 ml×gvs-1, while kinetics parameters were 292.7-344.7 ml×gvs-1, 0.08-0.11 d-1, and 24-42.5 ml×(gvs×d)-1, for ymax, k, and r, respectively. The main factors affecting biomethane production were substrate-to-inoculum ratio and biochar share. No specific effect between biochar types on biomethane yield was found. An increase in BC share from 2 to 50% concerning specifics SIR results in biomethane production improvement in the range from 1.8% to 10%. The main factors affecting the quality of digestate (nutrients) were the quality of the used inoculum and the quantity of used substrate. The research results were complex and showed that the final effect of biochar supplementation depends not only on biochar properties but also on process operational parameters and the quality of the used feedstock.